Pemanfaatan Media Informasi Dinas Pendidikan Provinsi Jawa Barat - Maman Chatamallah; Nabiilah Safira Putri (UNISBA Press, 2023)
Abstract. The process of communication in the digital era has changed significantly and created a new mode of communication, especially in cyberspace, namely the internet. The internet contains media that can be used to disseminate information, one of which is the website. Researchers in their research will discuss